Effects of Testosterone Level on Lower Urinary Tract Symptoms. (September 2016) - Crawford, E. David; Poage, Wendy; Nyhuis, Allen; Price, David A.; Dowsett, Sherie A.; Muram, David
Lower urinary tract symptoms (LUTS) are common in older men and are frequently associated with benign prostatic hyperplasia (BPH). The relationship between BPH and endogenous total testosterone (TT) levels has been widely studied. The aim of this post hoc analysis was to determine the association between LUTS and endogenous TT levels in a subset of men participating in the 2013 Prostate Cancer Awareness Week, a U.S. community-based prostate cancer screening program. Men completed the International Prostate Symptom Score (I-PSS) questionnaire, prostate size was estimated by a digital rectal examination, and serum TT and prostate-specific antigen levels were measured. Mean TT levels (ng/dl) did not significantly correlate with prostate size category ( r = +.03, p = .69): normal, 419.2 ( n = 106); enlarged, 394.7 ( n = 71); abnormal, 416.4 ( n = 7); and abnormal/suspicious, 515.2 ( n = 19). Mean TT levels (ng/dl) did not significantly correlate with I-PSS category ( r = −.06, p = .40): none, 468.5 ( n = 15); mild, 414.0 ( n = 138); moderate, 397.4 ( n = 66); and severe, 437.9 ( n = 7). Mean TT levels (ng/dl) did not significantly correlate with I-PSS quality of life rating ( r = −.13, p = .055): delighted, 474.5 ( n = 43); pleased, 424.6 ( n = 65); mostly satisfied, 361.2 ( n = 63); mixed, 448.2 ( n = 29); mostly dissatisfied, 337.2 ( n = 17); and unhappy, 435.8 ( n = 6). Adjustment for prostate size or prostate-specific antigen levels yielded similar findings. In conclusion, endogenous TT levels did not correlate with LUTS or prostate size, and these findings support the saturation theory in which TT is not able to induce further androgen-stimulated prostate tissue growth due to receptor saturation. Any worsening of LUTS following testosterone replacement therapy in hypogonadal men may be related to stimulation of prostatic cells previously deprived of testosterone.